Kinetic Studies of Heterogeneous Reactions of Polycyclic Aromatic Hydrocarbon Aerosols with NO3 Radicals - Liu, Changgeng; Zhang, Peng; Yang, Bo; Wang, Youfeng; Shu, Jinian (Environmental science & technology, 2012)
Polycyclic aromatic hydrocarbons (PAHs) and their derivates are mutagenic and carcinogenic substances widely distributed in the atmospheric environment. In this study, effective rate constants for heterogeneous reactions of NO3 radicals with five 4-ring PAHs [benzo[a]anthracene (BaA), chrysene (Ch), pyrene (Py), 1-nitropyrene (1-NP), and 1-hydroxypyrene (1-OHP)] adsorbed on suspended azelaic acid particles are investigated by a mixed-phase relative rate method with gas-phase isoprene as the reference substance. The concentrations of suspended PAH particles and gas-phase isoprene are monitored concurrently by a real-time vacuum ultraviolet photoionization aerosol time-of-flight mass spectrometer (VUV-ATOFMS) and an online atmospheric gas analysis mass spectrometer, respectively. The obtained effective rate constants for the reactions of BaA, Ch, Py, 1-NP, and 1-OHP particles with NO3 radicals are 4.3 × 10–12, 4.0 × 10–12, 6.4 × 10–12, 1.3 × 10–12, and 1.0 × 10–11 cm3·molecule–1·s–1, respectively, and their corresponding atmospheric lifetimes range from several minutes to half an hour at the NO3 radical concentration of 5 × 108 molecules·cm–3. In addition, the NO3 uptake coefficients on particulate PAHs are estimated according to the consumption of PAHs under the exposure of NO3 radicals. The experimental results of these heterogeneous reactions in the aerosol state provide supplementary knowledge for kinetic behaviors of airborne PAHs particles.